Simultaneous trisomy 9q3 and monosomy 5p in two children with der(5), t(5;9)(p15.1;q34.13): report of an extended family. Issue 10 (October 1988) - Wellesley, D; Young, I D; Cooke, P; Callen, D F; Hockey, A
Abstract : We present a family segregating for t(5;9)(p15.1;q34.13). Two cases with der(5), t(5;9), resulting in a partial duplication 9q34.13----qter and partial deletion of 5p15.12----pter, were ascertained. The phenotypes were consistent with features of both the cri du chat and trisomy 9q3 syndromes.